Proceedings of the 2022 ACM Conference on Information Technology for Social Good 2022
DOI: 10.1145/3524458.3547240
|View full text |Cite
|
Sign up to set email alerts
|

Explaining food security warning signals with YouTube transcriptions and local news articles

Abstract: Food security is a major concern in many countries all over the world. After a relatively long period characterized by a positive trend, the number and severity of food insecurity situations has been growing again in recent years, with alarming projections for the near future. While several Early Warning Systems (EWS) exist to monitor this phenomenon and guide the interventions of governments and ONGs, such systems rely on a narrow set of data types, i.e., mainly satellite imagery and survey data. These data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The topic modeling findings of this study can be used in data triangulation with data related to food security from other sources, including sources that are not social media. Previous research has used topic modeling of YouTube and newspaper data and found some consistency between the regions discussing food security and household survey data on the food security risk of these same regions, potentially serving as early warning signals for at-risk areas [84]. Our study found that the topics in food security social media data reflected all the dimensions of food security as defined by the Food and Agriculture Organization [3] and Clapp et al [39] to different extents.…”
Section: Xsl • Fomentioning
confidence: 49%
See 1 more Smart Citation
“…The topic modeling findings of this study can be used in data triangulation with data related to food security from other sources, including sources that are not social media. Previous research has used topic modeling of YouTube and newspaper data and found some consistency between the regions discussing food security and household survey data on the food security risk of these same regions, potentially serving as early warning signals for at-risk areas [84]. Our study found that the topics in food security social media data reflected all the dimensions of food security as defined by the Food and Agriculture Organization [3] and Clapp et al [39] to different extents.…”
Section: Xsl • Fomentioning
confidence: 49%
“…These techniques could also include using multiple platforms of information-from news articles to different social media platforms and using search terms beyond hashtags-to capture a wider understanding. Infoveillance techniques also have the potential to track trends in the prevalence of food insecurity, thereby enabling the public health sector to improve some of the major effects of food insecurity on health status in a more proactive way by detecting early warning signals [84]. Currently, the prevalence of food insecurity is not completely understood or able to be tracked because of the difficulty in obtaining data and the use of different tools that do not measure all the dimensions of food security [96,97].…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…In addition to traditional NLP, word embedding [13] can be used to extract information. [14] uses word embedding vectors to derive spatio-temporal characteristics and special indicators from text documents describing food security problems. The method is then used for analyzing the food crisis in West Africa.…”
Section: Related Work a Rule Identificationmentioning
confidence: 99%
“…In this study, we examine the ability of text mining methods to extract and analyze the qualitative information used as proxies for the national and regional food situation and its evolution over the last ten years in Burkina Faso from a corpus of newspapers from the country. The aim is to provide explainable indicators complementary to the automatic predictions of food security scores, i.e., as the ones obtained in our previous works based on the application of machine learning approaches on heterogeneous [3] and textual [2] data.…”
Section: Introductionmentioning
confidence: 99%